СУЩЕСТВУЮЩИЕ ТРЕБОВАНИЯ И ПОДХОДЫ К ОРГАНИЗАЦИИ ПРИРОДОПОЛЬЗОВАНИЯ И ОХРАНЫ ОКРУЖАЮЩЕЙ СРЕДЫ НА ПРЕДПРИЯТИИ, МЕРЫ ПО ИХ УЛУЧШЕНИЮ - Костылева (Kostileva Natalia), Наталья Валерьевна; Микишева (Mikischeva Valentina), Валентина Ивановна (Географический вестник=Geographical bulletin, 2017)
Рассмотрены существующие требования и подходы к организации природопользования и охраны окружающей среды на предприятии. Изложены преимущества внедрения системы экологического менеджмента (СЭМ). Даны рекомендации по улучшению природоохранной деятельности на предприятии до внедрения СЭМ. EXISTING REQUIREMENTS AND APPROACHES TO ORGANIZATION OF USING NATURAL RESOURCES AND ENVIRONMENT PROTECTION AND IMPROVEMENT OF THEM AT THE ENTERPRISE Existing and most widespread environmental protection activity organization problems at the enterprise are considered. Modern environmental manage ways are specified. Several simple and effective recommendations for international experience approach and for the improvement of enterprises environment protection activity results are given.